2015
DOI: 10.1101/lm.038844.115
|View full text |Cite
|
Sign up to set email alerts
|

Atypical PKCs in memory maintenance: the roles of feedback and redundancy

Abstract: Memories that last a lifetime are thought to be stored, at least in part, as persistent enhancement of the strength of particular synapses. The synaptic mechanism of these persistent changes, late long-term potentiation (L-LTP), depends on the state and number of specific synaptic proteins. Synaptic proteins, however, have limited dwell times due to molecular turnover and diffusion, leading to a fundamental question: how can this transient molecular machinery store memories lasting a lifetime? Because the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 111 publications
(175 reference statements)
0
52
0
Order By: Relevance
“…Although prior studies have implied that ZIP does not impair spontaneous or evoked network activity, these studies only reported data for time windows beyond 2 h after infusion (Madroñal et al, 2010;Barry et al, 2012). Our study demonstrates significant inhibition of local network activity within that time frame.…”
Section: Impact Of Molecular Manipulations On Activitymentioning
confidence: 37%
See 3 more Smart Citations
“…Although prior studies have implied that ZIP does not impair spontaneous or evoked network activity, these studies only reported data for time windows beyond 2 h after infusion (Madroñal et al, 2010;Barry et al, 2012). Our study demonstrates significant inhibition of local network activity within that time frame.…”
Section: Impact Of Molecular Manipulations On Activitymentioning
confidence: 37%
“…This timing is similar to the suppressive effect of anisomycin (Sharma et al, 2012), but slower than agents acting directly on ion channels (present study and van Duuren et al, 2007), which suggests that it acts via a (yet unknown) biochemical signaling mechanism. Furthermore, the presence of epileptiform activity after ZIP administration in seven of 12 (ϳ60%) of our ZIP experiments (despite the fact that urethane anesthesia is known to dampen seizure activity; Cain et al, 1989) presents additional interpretational problems for prior studies. For example, although ZIP was suggested to interfere with place cell stability (Barry et al, 2012), electrophysiological data were only reported after at least a 2 h period after ZIP administration.…”
Section: Impact Of Molecular Manipulations On Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…This inhibitor may not be specific for PKMz, and genetic inactivation models of PKMz activity have failed to alter memory processes that were suggested to be dependent on PKMz (Lee et al, 2013a;Volk et al, 2013). Other atypical PKC members might compensate the genetic inactivation of PKMz, suggesting redundance of regulating mechanisms (Jalil et al, 2015).…”
Section: A Cocaine a Stimulant And Local Anestheticmentioning
confidence: 99%